2011
DOI: 10.1111/j.1600-0501.2011.02299.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings from cone beam computed tomography of the maxillofacial region: a descriptive retrospective study

Abstract: This study underscores the need to thoroughly examine all CBCT volumes for clinically significant findings within and beyond the region of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
147
6
44

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(218 citation statements)
references
References 22 publications
21
147
6
44
Order By: Relevance
“…In this study, no SBC was found; one reason may be the low prevalence of the finding, which ranges between 0.08% and 0.4% (Allareddy et al, 2012;Assaf et al, 2014;Correll et al, 1980;Price et al, 2012). Additionally, a reason may be that the finding appears more often in male patients and at a mean age of 45e60 years (Allareddy et al, 2012;Correll et al, 1980;Murdoch-Kinch, 2009;Schneider et al, 2014a;Shimizu et al, 2006).…”
Section: Stafne Bone Cavity (Sbc)mentioning
confidence: 60%
See 3 more Smart Citations
“…In this study, no SBC was found; one reason may be the low prevalence of the finding, which ranges between 0.08% and 0.4% (Allareddy et al, 2012;Assaf et al, 2014;Correll et al, 1980;Price et al, 2012). Additionally, a reason may be that the finding appears more often in male patients and at a mean age of 45e60 years (Allareddy et al, 2012;Correll et al, 1980;Murdoch-Kinch, 2009;Schneider et al, 2014a;Shimizu et al, 2006).…”
Section: Stafne Bone Cavity (Sbc)mentioning
confidence: 60%
“…Other studies that examined the prevalence of CAC reported findings ranging from 1.5% to 43% (Allareddy et al, 2012;Damaskos et al, 2015;Price et al, 2012). This variation shows the potential difficulty of diagnosing CAC.…”
Section: Carotid Artery Calcification (Cac)mentioning
confidence: 95%
See 2 more Smart Citations
“…With the development of three-dimensional (3D) imaging modalities, cone beam computed tomography (CBCT) has gained widespread acceptance in dentistry. It provides high resolution, cross-sectional view and diagnostic reliability at lower costs and radiation doses [1,12,18]. It allows detailed multiplanar evaluation of maxillofacial region to be conducted for further analysis of the anatomical structures which could not have been detected by conventional imaging modalities [4,6,10].…”
Section: Introductionmentioning
confidence: 99%